Economic Transformation, Population Growth, and the Long-Run World Income Distribution - Chamon, Marcos; Kremer, Michael (Washington, D.C. : International Monetary Fund, 2006)
This paper considers the long-run evolution of the world economy in a model where countries' opportunities to develop depend on their trade with advanced economies. As developing countries become advanced, they further improve trade opportunities for the remaining developing countries. Whether or not the world economy converges to widespread prosperity depends on the population growth differential between developing and advanced economies, the rate at which countries develop, and potentially on initial conditions. A calibration using historical data suggests that the long-run prospects for lagging developing regions, such as Africa, likely hinge on the sufficiently rapid development of China and India.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet